Passive Construction of Transitive Verbs in Pulau Rengas Language - Awliya Rahmi (Diwan: Jurnal Bahasa dan Sastra Arab, 2018)
This study focuses on examining the passive construction in Pulau Rengas language. The data of this study is the passive construction in sentences uttered by Pulau Rengas natives. The data were collected by doing deep interview and recording techniques. The data were then analyzed by applying the syntax theories focusing on Maggie and Tallerman’s. The result of this research shows that passive construction in this language is related to the phonological characteristic of the language itself. Pulau Rengas language is a diphthongal language. This characteristic affects the process of passive construction in this language. While most of language marks the passive verbs morphologically, Pulau Rengas language marks the passive verbs by omitting the prefix of the active verbs. In certain verbs, the passive forms are also marked phonologically depending on the first sound of the verb.